Teaching Persian for Academic Purposes: Evaluating the Textbook of Nabz-e Zendegi (Pulse of Life) for International Students Based on Miekley’s Checklist - Amirreza Vakilifard; Nadia Ahmadi Khalkhali (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
It would be significant to analyze the content of these educational resources to see whether they are in line with the students’ needs.  Miekley’s (2005) checklist is considered an effective criterion for the selection and analysis of language teaching materials. The participants were (a) 25 Persian language teachers teaching Persian to non-Persian language learners and (b) 32 non-Persian language learners, majoring in different medicine sciences in Iranian medical universities. They were asked to analyze the textbook entitled as “Pulse of Life” (Nabze Zendegi) (1385) based on categories in Miekley’s (2005) proposed checklist. Descriptive statistics were employed to separately analyze the data of two groups; the results obtained were compared and contrasted. Given the first section, namely, textbook, teacher participants claimed that the textbook was structurally well-designed and it included attractive content and sub-contents as well as relevant vocabularies and grammar structures. However, student volunteers believed that tasks and activities along with grammar structures and vocabularies were not appropriately presented in this textbook. Two groups of participants perceived that the sub-sections of general characteristics, background information, and methodology guide were not suitable. However, they considered the context section appropriate. Teachers graded the vocabulary subsection, and the students ranked the grammar subsection in the second status. Subsections of passage attraction and book appearance were ordered in the third rank. The findings of this investigation could be helpful for researchers and teachers in evaluating the efficiency and appropriateness of instructional resources, possibly available in the instructional resources of teaching Persian to non-Persian language learners.